Isolasi Senyawa Alkaloid Bahan Alam - Bismar Al Bara; Faizal Auladi Rivianto; Nurlaela Nurlaela; Sulastri Sulastri (Jurnal Health Sains, 2021)
This study aims to isolate and identify alkaloid group compounds from some plant samples used. Alkaloid compounds are the most common organic compounds found in nature. This method of review literature study comes from library reviews and other studies by collecting a variety of relevant literature. Almost all alkaloids are native to plants and are widespread in various types of plants. Examination of plants containing alkaloids there are several stages, namely drying, extraction, fractionation, and isolation. Isolation of alkaloid compounds can be done using several methods. In the extraction process used 3x24 hours maceration method, then the fractionation process using Vacuum Liquid Chromatography (KCV) with the silent phase of silica gel and n-hexan motion phase: ethyl acetate and fractions are isolated again using Gravitational Column Chromatography (KKG) with a silent phase of silica gel and nheksan motion phase: ethyl acetate. The fraction is analyzed for purity using Thin Layer Chromatography (KLT) with a still phase of silica gel254.